Surgical validation of functional magnetic resonance urography in the study of ureteropelvic junction obstruction in a pediatric cohort. Issue 2 (April 2019) - Wong, M.C.Y.; Sertorio, F.; Damasio, M.B.; Incarbone, V.; Beati, F.; Bodria, M.; Pistorio, A.; Ghiggeri, G.M.; Magnano, G.M.; Mattioli, G.
Summary: Introduction: Ureteropelvic junction obstruction (UPJO) is one of the most common urological diseases in children. The etiology can be intrinsic, extrinsic (crossing vessel [CV] or adhesions), or mixed. To date, ultrasonography and scintigraphy are considered gold-standard imaging techniques for the study of UPJO. Functional magnetic resonance urography (fMRU) combines anatomical and functional information and has been recently evaluated for the detection of CVs in UPJO. Objective: The objective of the study was to evaluate the concordance between fMRU and surgery in determining the etiology of UPJO and the presence of obstructing/non-obstructing CVs. Study design: Patients with unilateral hydronephrosis who underwent surgery after an fMRU were included in the sample. Surgical data regarding the etiology of UPJO were compared with radiological results. The etiology was divided into intrinsic, extrinsic due to CV, extrinsic due to adhesions, and mixed or cicatricial (postoperative). The concordance was calculated by means of the Cohen's kappa coefficient. Results: The observed agreement between fMRU and surgical findings regarding the etiology and the presence of CV were 83.2% and 89.4%, respectively (with substantial Cohen's kappa coefficient). The sensitivity and specificity of fMRU were 0.84 and 0.93, respectively; the positive predictive value (PPV) and negative predictive value (NPV) were 0.889 and 0.897, respectively. The observed agreement regarding the type of vessel was 88.3% with a Cohen's kappa coefficient of 0.787 (substantial). Discussion: In children with hydronephrosis, it is very important for the surgeon to quantify the extent of dilation, define the etiology of the obstruction, and the presence or absence of CVs. fMRU is a 'one-stop-shop' technique which provides both anatomical and functional information showing a high concordance with surgical findings, avoiding radiation exposure. Conclusions: fMRU should be considered a valid imaging technique in the study of pediatric UPJO, as it provides the surgeon with important information regarding the etiology of the obstruction for the preoperative planning.fMRU image showing the presence of CV as etiologic cause of the obstruction.